2021
DOI: 10.1016/j.bbrep.2021.100990
|View full text |Cite
|
Sign up to set email alerts
|

Comparative lipid and uric acid suppressing properties of four common herbs in high fat-induced obese mice with their total phenolic and flavonoid index

Abstract: Our present study was designed to investigate the comparative anti-obesity efficacy of ethanolic extract of Azadirachta indica A. Juss. , Trigonella foenum-graecum L. , Allium sativum L. and Zingiber officinale Roscoe in high fat-induced mice with their total phenolic and flavonoid profile. Total phenolic and flavonoid content were determined by Folin–Ciocalteu's and Aluminium chloride UV method respectively. In our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These reagents were manufactured by the standard company Human Diagnostics Worldwide, Germany. TC was determined by an enzymatic colorimetric method (endpoint) [ 15 ], and TG was estimated by the enzymatic colorimetric GPO-PAP method [ 16 ]. HDL-C was measured by phosphotungstate method [ 17 ] by using Mindray BA-88A Semi-Auto Clinical Chemistry Analyzer (Crown Healthcare, Tanzania).…”
Section: Methodsmentioning
confidence: 99%
“…These reagents were manufactured by the standard company Human Diagnostics Worldwide, Germany. TC was determined by an enzymatic colorimetric method (endpoint) [ 15 ], and TG was estimated by the enzymatic colorimetric GPO-PAP method [ 16 ]. HDL-C was measured by phosphotungstate method [ 17 ] by using Mindray BA-88A Semi-Auto Clinical Chemistry Analyzer (Crown Healthcare, Tanzania).…”
Section: Methodsmentioning
confidence: 99%
“…The normal range of uric acid in blood is 360 and 420 μM in women and men, respectively, but close to neutral pH, such as in case of blood, concentrations >360 μM can initiate precipitation that leads to the accumulation of monosodium urate crystals in joint tissue interstitial spaces and gout ( 26 ). Increase in serum uric acid level causes weight gain thus leads to obesity which causes increase in uric acid synthesis and hinder its excretion via kidneys thus causing expansion in hyperuricemia ( 27 ). Liquid chromatography, bi-enzymatic colorimetry, capillary electrophoresis, and fluorescence spectroscopy are just a few of the systematic methods that have been developed to detect uric acid range in blood serum and urine of humans.…”
Section: Potential Health Applications Of Quercetinmentioning
confidence: 99%
“…12,13 Due to the anti-inflammatory and antioxidant capacity of flavonoids, 14,15 studies have shown that flavonoids can affect the activity of XO, treat gout from the root and reduce the synthesis of uric acid. 7,16 Therefore, flavonoids have become a research hotspot for alleviating uric acid. 1 Some flavonoids, such as luteolin and apigenin, have promising therapeutic effects on gout.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids widely exist in fruits, vegetables, and other foods in daily life 12,13 . Due to the anti‐inflammatory and antioxidant capacity of flavonoids, 14,15 studies have shown that flavonoids can affect the activity of XO, treat gout from the root and reduce the synthesis of uric acid 7,16 . Therefore, flavonoids have become a research hotspot for alleviating uric acid 1 .…”
Section: Introductionmentioning
confidence: 99%